It's time to (climate) change the way we teach: Addressing anthropogenic climate change in social science classrooms. Issue 2 (1st June 2021) - Shoreman-Ouimet, Eleanor
Abstract: This article outlines pedagogical practices and methodologies for increasing student engagement in the classroom and in the broader community on the topic of climate change. The emphases are placed on (1) preliminary assessments of student understanding and emotional responses to the topic of climate change, (2) assignments that enable student groups to assess and increase campus-wide awareness of various aspects of climate change, and (3) public engagement and service-learning opportunities that allow students to expand their impact beyond the local campus and into their broader community. These practices have proven effective, for large format lecture courses as well as smaller seminar-style courses, in encouraging student participation, overcoming apathy and motivating student effort and action far beyond what can be stimulated by traditional classroom assignments and assessments.